EFEKTIVITAS SELF-ASSESSMENT DAN PEER-ASSESSMENT TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR PADA PEMBELAJARAN IPS - Nadya Lufikasari; Nuansa Bayu Segara; Silvi Nur Afifah; Muhammad Ilyas Marzuqi (STKIP Subang, 2026)
This study was motivated by the importance of developing students' critical thinking skills and independent learning abilities in 21st-century social studies education. However, learning and assessment processes that remain teacher-centered result in students being less engaged in the process of reflection and evaluation of their learning. Therefore, this study aims to analyze the effectiveness of self-assessment and peer assessment on students' critical thinking skills and learning autonomy in project-based social studies learning for eighth-grade students at SMPN 36 Surabaya. This study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The sample consisted of an experimental class that received project-based social studies instruction integrated with self-assessment and peer assessment, and a control class that used conventional instruction. Data were collected through pretests and posttests, self-assessment questionnaires, peer assessment forms, and observations. Data analysis involved the N-Gain test and hypothesis testing. The results of the study indicate that the implementation of self-assessment and peer assessment is effective in enhancing students' critical thinking skills and independent learning. Students who engage in self-assessment and peer assessment demonstrate greater ability to reflect, evaluate, analyze, and manage their learning process independently compared to students who participate in conventional learning. Thus, self-assessment and peer assessment can serve as effective assessment strategies to support project-based social studies learning and to develop students' critical thinking skills and learning independence.